2015
DOI: 10.1177/0148607115609566
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Dosing Study of Glucagon‐Like Peptide 2 in Children With Intestinal Failure

Abstract: GLP-2 was well tolerated in children, with a pharmacokinetic profile similar to that of adults. There were no changes in endogenous GLP-2 release or metabolism. These results suggest that GLP-2 ligands may be safely used in pediatric patients; larger trials are suggested to investigate nutritional effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
0
26
1
1
Order By: Relevance
“…Thus, for patients dependent on TPN, a promising strategy to improve intestinal growth and maintain epithelial barrier function has been with the use of exogenous growth factors 56 . GLP-2 and GLP-2 analogues have been used successfully in TPN patients to promote intestinal adaptation, improve small intestinal surface area and absorptive function, and can facilitate withdrawal from parenteral nutrition 5, 6, 57. Similarly, EGF has been shown to have considerable benefit for pediatric patients with SBS and necrotizing enterocolitis 58, 59.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for patients dependent on TPN, a promising strategy to improve intestinal growth and maintain epithelial barrier function has been with the use of exogenous growth factors 56 . GLP-2 and GLP-2 analogues have been used successfully in TPN patients to promote intestinal adaptation, improve small intestinal surface area and absorptive function, and can facilitate withdrawal from parenteral nutrition 5, 6, 57. Similarly, EGF has been shown to have considerable benefit for pediatric patients with SBS and necrotizing enterocolitis 58, 59.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed understanding of the signaling pathways responsible for TPN-related intestinal complications therefore is needed to improve therapeutic options and clinical outcomes for patients dependent on TPN. Teduglutide, a stable analog of glucagon-like peptide 2 (GLP-2), is one new therapeutic approach that is undergoing extensive clinical trials for the treatment of patients with intestinal failure 5, 6. A recent report showed long-term teduglutide treatment was effective in reducing parenteral support in patients with short-bowel syndrome (SBS), 6 however, the mechanisms underlying the beneficial actions of GLP-2 and its analogs in the gut are complex and still poorly defined.…”
mentioning
confidence: 99%
“…Multiple growth factors have been identified that enhance adaptation in animal models, such as growth hormone, insulin-like growth factor-1, epidermal growth factor, glucagon-like peptide 2, and steroids 10 . Of these, growth hormone and glucagon-like peptide 2 have shown promising results in improving nutrient absorption and weight gain in human patients with SBS 11, 12, 13. In our study, RNA sequencing analysis did not show any significant difference in levels of mRNA for growth hormone receptor, epidermal growth factor, insulin-like growth factor-1, epidermal growth factor receptor, or glucagon-like peptide 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In PN-dependent neonates with IF, Sigalet and colleagues reported positive correlation between serum GLP-2 levels and tolerance of enteral feeds [12]. In adult studies and preliminary data on children, GLP-2 and its long-acting synthetic analog, teduglutide, have been shown to improve nutrient and fluid absorption, weight gain, and to reduce PN requirements [8,13,14]. In this study, serum GLP-1 levels were decreased during PN, while serum GLP-2 levels were increased irrespective of whether or not patients were currently receiving PN.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IF, lack of feed-stimulated GLP-2 response may lead to poor intestinal adaptation [4,5,12]. Discovery of enterotrophic effects of GLP-2 has led to novel emerging treatment options in patients with IF [13,14]. A GLP-2 analog teduglutide has been shown to improve nutrient and fluid absorption, endorse mucosal hyperplasia, and decrease PN requirement in IF patients [13,15,16].…”
Section: Introductionmentioning
confidence: 99%